Azeotropy Breaking in Refrigerant Blends with Ionic Liquids - Mazur, V.; Haddad, S.; Nikitin, D. (Journal of Applied Solution Chemistry and Modeling, 2014)
The principal aim of this work is to study azeotropy breaking in the refrigerant blends with ionic liquids (IL). The global phase diagram approach is applied to correlate azeotropic data for binary mixtures based only on critical properties and acentric factor of the individual components in mixtures. Analytical expressions to predict azeotropy phenomena in terms of critical parameters of pure components and binary interaction parameters are given. The eventual azeotropy appearance in the refrigerant - IL blends is discussed and conclusion about highly improbable azeotropic blend formation for these systems is given. Global phase behavior of ionic liquid - industrial refrigerant blends is analyzed and possible III, IV and/or V types according to the classification scheme of Scott and van Konynenburg [1] are established. The azeotropy breaking in binary refrigerant mixtures with ionic liquid adding is predicted.